Low-density lipoprotein (LDL)-antioxidant biflavonoids from garcinia madruno (2013)
ABSTRACT: Six biflavonoids were isolated from G. madruno, one of which, 7''-O-(6''''-acetyl)-glucoside of morelloflavone, is a new compound identified on the basis of 1D, 2D NMR (HMQC and HMBC) spectroscopic methods and chemical evidence. The antioxidant activity of the biflavonoids against low-density lipoprotein (LDL) peroxidation induced with Cu2+, was studied by means of a TBARS assay. The antioxidant potential of a biflavonoid fraction (BF) was also evaluated and correlated with its biflavonoid content. The flavanone-(3→8'')-flavone biflavonoids displayed antioxidant activity, particularly morelloflavone, which was significantly more potent than quercetin, with a CE50 of 12.36 μg/mL. Lipid peroxidation, was also significantly reduced in the presence of the BF (EC50 = 11.85 μg/mL). These results suggest that the BF is an excellent antioxidant.